2023
DOI: 10.1101/2023.11.11.566377
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The evolutionary age-range size relationship is modulated by insularity and dispersal in plants and animals

Adriana Alzate,
Roberto Rozzi,
Julian A. Velasco
et al.

Abstract: Earth is home to millions of plant and animal species, with more than 40 thousand species facing extinction worldwide (Diaz et al. 2019). Species’ range size is particularly important in this context because it influences extinction risk (Purvis et al. 2000, Gaston & Fuller 2009), but the causes underlying the wide natural variation in range size remain poorly known. Here, we investigate how evolutionary age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The lowest error in species age estimation was observed under scenarios of bifurcating speciation. This is the implicit assumption of most studies using approximations of species ages (Alzate et al, 2023; Freer et al, 2022; Kennedy et al, 2022), even though it is at odds with the assumption of all birth-death models used in the molecular clock analyses that estimate the phylogenetic trees in the first place (Gernhard, 2008; Nee et al, 1994; Stadler, 2013). Despite the lower error, our simulations showed that both extinction and missing lineages can lead to a substantial decrease in accuracy (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lowest error in species age estimation was observed under scenarios of bifurcating speciation. This is the implicit assumption of most studies using approximations of species ages (Alzate et al, 2023; Freer et al, 2022; Kennedy et al, 2022), even though it is at odds with the assumption of all birth-death models used in the molecular clock analyses that estimate the phylogenetic trees in the first place (Gernhard, 2008; Nee et al, 1994; Stadler, 2013). Despite the lower error, our simulations showed that both extinction and missing lineages can lead to a substantial decrease in accuracy (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, several studies have used the length of terminal branches in time-calibrated phylogenies as a proxy for the age of extant species, an approximation that we hereafter refer to as "phylogenetic age" (Alzate et al, 2023;Davies et al, 2011;Gaston & Blackburn, 1997;Johnson et al, 2002;Pie & Caron, 2023;Sonne et al, 2022;Tanentzap et al, 2020;Verde Arregoitia et al, 2013). These phylogenetic ages have been used as the basis to test for links between species age and current extinction risks (Tanentzap et al, 2020;Verde Arregoitia et al, 2013) and to assess various correlations with evolutionary, biogeographical, and ecological patterns in living species (Alzate et al, 2023;Freer et al, 2022;Kennedy et al, 2022;Pie & Caron, 2023) While several studies have used phylogenetic age at face value for species age (e.g., Johnson et al 2002;Tanentzap et al 2020;Verde Arregoitia et al 2013), their potential deviation from the true species ages remains unclear. Specifically, we identify three nonmutually exclusive shortfalls that can lead to over-or underestimation of species ages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…climate) may change in the future (Farnsworth et al, 2023;Taylor, 2004) and whether it can adequately adapt. With the rapid development in phylogenetic studies (Alzate et al, 2023;Ramirez-Barahona et al, 2020), absolute age data are easier to be estimated (although extinct species are missing from the analysis) and we could examine how their current range sizes might be related to their absolute ages (times since species formation), which is also important for understanding many macroecological and biogeographical patterns and processes (Gaston & Blackburn, 1997). For example, all living species are a 'mixed bag' that includes species' ranges either expanding or contracting, but their relative fractions remain unknown.…”
Section: The Rel Ative Vs Absolute Ag E: Why Ag E Mat Ter S?mentioning
confidence: 99%
“…Some recent studies also show that species richness is strongly associated with species range size (Guo et al, 2022; see also Shipley & McGuire, 2023). Recently, species' age has been increasingly cited as a possible major factor that may have contributed to determining species range size (Alzate et al, 2023;Guo et al, 2022;Webb & Gaston, 2000), but its contribution has rarely been examined with empirical data, especially for large species groups (e.g. vertebrate classes) and at a global scale (Gaston & Blackburn, 1997;Webb & Gaston, 2000).…”
mentioning
confidence: 99%